Frequency of Parapneumonic Effusion in Patients with Community-Acquired Pneumonia - Rafia khan; shah, Sajjad Ali; Lailoma Kakar; Atif Rahim; Amir Ali; Ejaz Ahmad (International Journal of Pathology, 2026)
Background: Community-acquired pneumonia (CAP) is a significant cause of morbidity and hospitalization worldwide. Parapneumonic effusion (PPE), the accumulation of pleural fluid secondary to pneumonia, is a common complication that can increase disease severity and negatively affect clinical outcomes if not identified early. Objective: To determine the frequency of parapneumonic effusion among patients with community-acquired pneumonia and to evaluate its association with selected demographic and clinical characteristics. Methods: This cross-sectional study was conducted in the Department of Pulmonology at MTI Mardan Medical Complex, Mardan, over a six-month period from September 2025 to February 2026. A total of 107 patients diagnosed with community-acquired pneumonia were included in the study. Demographic characteristics, clinical history, and radiological findings were recorded using a structured data collection form. Data were analyzed using statistical software. Categorical variables were presented as frequencies and percentages. Stratification was performed based on age and gender, and the chi-square test was applied to assess associations. A p-value ≤0.05 was considered statistically significant. Results: Among the 107 patients, 54 (50.5%) were males and 53 (49.5%) were females, with a mean age of 49.18 ± 14.88 years. Parapneumonic effusion was detected in 43 (40.2%) patients. Of these, 37 (34.6%) had uncomplicated effusion and 6 (5.6%) had complicated effusion. Conclusion: Parapneumonic effusion is a frequent complication among patients with community-acquired pneumonia. Early detection and appropriate management may help reduce complications and improve patient outcomes.